Matplotlib 3.0 Cookbook Over 150 recipes to create highly detailed interactive visualizations using Python - Poladi, Srinivasa Rao (Packt Publishing Limited, 2018)
bBuild attractive, insightful, and powerful visualizations to gain quality insights from your data/b h4Key Features/h4 ulliMaster Matplotlib for data visualization /li liCustomize basic plots to make and deploy figures in cloud environments /li liExplore recipes to design various data visualizations from simple bar charts to advanced 3D plots /li /ul h4Book Description/h4 Matplotlib provides a large library of customizable plots, along with a comprehensive set of backends. Matplotlib 3.0 Cookbook is your hands-on guide to exploring the world of Matplotlib, and covers the most effective plotting packages for Python 3.7. With the help of this cookbook, you'll be able to tackle any problem you might come across while designing attractive, insightful data visualizations. With the help of over 150 recipes, you'll learn how to develop plots related to business intelligence, data science, and engineering disciplines with highly detailed visualizations.